2014
DOI: 10.1017/s1751731114001724
|View full text |Cite
|
Sign up to set email alerts
|

Effects of birth weight and maternal dietary fat source on the fatty acid profile of piglet tissue

Abstract: This study aimed to investigate the effects and possible interactions of birth weight and n-3 polyunsaturated fatty acid (PUFA) supplementation of the maternal diet on the fatty acid status of different tissues of newborn piglets. These effects are of interest as both parameters have been associated with pre-weaning mortality. Sows were fed a palm oil diet or a diet containing 1% linseed, echium or fish oil from day 73 of gestation. As fish oil becomes a scarce resource, linseed and echium oil were supplemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Lowering the ratio of ω6:ω3 PUFAs by adding linseed oil to the maternal diet can decrease ω6:ω3 ratio in colostrum and milk by enriching ALA concentration [1], thus, increasing concentrations of ALA in piglet liver, brain, and muscle tissues [37], plasma, carcass [38], and intestinal mucosa [39]. Our results are consistent with the findings of Yao et al [1] when offering high ALA combined with the low LA diet.…”
Section: Discussionsupporting
confidence: 90%
“…Lowering the ratio of ω6:ω3 PUFAs by adding linseed oil to the maternal diet can decrease ω6:ω3 ratio in colostrum and milk by enriching ALA concentration [1], thus, increasing concentrations of ALA in piglet liver, brain, and muscle tissues [37], plasma, carcass [38], and intestinal mucosa [39]. Our results are consistent with the findings of Yao et al [1] when offering high ALA combined with the low LA diet.…”
Section: Discussionsupporting
confidence: 90%
“…Study also showed that the addition of animal-based PUFA, such as fish oil, has led to improved DHA deposition in piglet tissue compared to piglet supplemented by plant-based PUFA. The same study also stated that maternal supplementation of PUFA increases piglet brain DHA that correlates with birthweight (24) . A study also showed that the addition of DHA in piglets' diet has shown to increase N-acylethanolamine, a type of cannabinoid receptor ligand, in specific brain regions such as brainstem, auditory cortex, cerebellum, and striatum, up to ten fold compared to DHA-deficient diet (25) .…”
Section: Dha Studies In Animal Modelsmentioning
confidence: 74%
“…The highest levels of FA found in this tissue were palmitic (C16:0), stearic (C18:0), oleic (C18:1 n-9), arachidonic (C20:4 n-6) and docosahexaenoic (C22:6 n-3). Authors (Palmquist et al, 2009;Francine et al, 2010;Tanghe et al, 2014) mention that nerve tissue requires high amounts of DHA for neuronal function and mammals are able to synthesize DHA from its precursor Alpha-linoleic acid by a series of enzymatic reactions that enlarge it to C24:6 n-3, followed by beta-oxidation to convert it to DHA, which can be metabolically utilized. In the brain it is used mainly for phospholipid synthesis as a part of neuron membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Fatty acids (FA) of the n-3 series are a structural component of the phospholipid membrane of neurons and are found in high concentrations in the brain and retina. Their use in diets for sows has been shown to improve foetal development and neonatal vigour (Tanghe et al, 2014;Francine et al, 2010). The synaptic membranes of the brain contain high amounts of docosahexaenoic acid (DHA) and arachidonic acid (ARA), which have been shown to intervene in the learning process, exploration and survival of piglets (Farmer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%